Vagueness in Communication International Workshop, VIC 2009, held as part of ESSLLI 2009, Bordeaux, France, July 20-24, 2009. Revised Selected Papers - Nouwen, Rick; van Rooij, Robert; Sauerland, Uli; Schmitz, Hans-Christian (Lecture Notes in Artificial Intelligence,, 2011)
This book constitutes the proceedings of the International Workshop on Vagueness in Communication, VIC 2009, held as part of ESSLLI 2009, in Bordeaux, France, July 20-24, 2009. The 11 contributions presented shed a light on new aspects in the area of vagueness  in natural language communication. In contrast to the classical instruments of dealing with vagueness - like multi-valued logics, truth value gaps or gluts, or supervaluations - this volume presents new approaches like context-sensitivity of vagueness, the sharpening of vague predicates in context, and the modeling of precision levels.